Online Teaching: Perceptions, Challenges and Opportunities during and beyond Covid-19 Pandemic among Secondary School Teachers - Varghese, Jijo; Musthafa, M.N. Mohamedunni Alias (SAINTIS Publishing, 2022)
Due to the outbreak of COVID-19 and closure of educational institutions, a shift from offline to online classes was essential to maintain academic activities carry on. This necessitated to think the educators regarding their preparedness, concerns and challenges related to technical constraints while shifting the academic activities completely to digital mode. The purpose of the study emanated from the need to understand the perceptions, challenges, and opportunities of online teaching during COVID-19 experienced by the teachers. Survey method was adopted for the study and data collected from 328 secondary school teachers who were working both in private and public schools of Kerala, a southern state of India. The results of the study revealed that around 94.4% of the participants of the study agreed that they had proper accessibility to digital devices and tools to carry out online classes during the COVID-19 pandemic and 76% had reported that they had enough knowledge and competencies in handling these tools effectively for conducting the online classes. Approximately 73% of the teachers who took part in the survey confirmed that they make use of google classroom as a learning management system and 59.7% used google meet, 21.4% used Zoom and rest of them made use various digital tools for online content delivery. A large majority (78%) of the participants agreed that they would go for a blended class even after the COVID-19 pandemic where they make use of the possibilities of online mode of learning in the regular classes.